B Cells in Rheumatoid Arthritis：Pathogenic Mechanisms and Treatment Prospects - Wu, Fengping; Gao, Jinfang; Kang, Jie; Wang, Xuexue; Niu, Qing; Liu, Jiaxi; Zhang, Liyun (Frontiers in Immunology, 2021)
Rheumatoid arthritis (RA) is a common, chronic, systemic autoimmune disease, and its clinical features are the proliferation of joint synovial tissue, the formation of pannus and the destruction of cartilage .The global incidence of RA is about 1%, and it is more common in women. The basic feature of RA is the body's immune system disorders, which mainly include auto-reactive B cells, anti-citrullinated protein antibodies (ACPA) and rheumatoid factor (RF) and other autoantibodies abnormally increase in the body of RA patients. B cell depletion therapy has well proved the important role of B cells in the pathogenesis of RA, and the treatment of RA with B cells as a target has also been paid more and more attention. Although the inflammatory indicators in RA patients receiving B-cell depletion therapy have been significantly improved, the risk of infection and cancer has also increased, which suggests that we need to deplete pathogenic B cells instead of all B cells. However, at present we cannot distinguish between pathogenic B cells and protective B cells in RA patients. After studying this point, we can develop new disease treatments for pathogenic B cells, which will open the way for precise treatment of RA.